Pédagogie de l’inclusion : fondements, définition, défis et perspectives - Vienneau, Raymond (Éducation et francophonie, 2002)
This article is devoted to one of the eight complementary components of the concept of “the Pedagogy of Actualization” proposed by the Faculté des sciences de l’éducation of the Université de Moncton. The inheritor of scholastic integration and normalization movements, inclusion pedagogy now proposes nothing less than the full-time pedagogical integration of all students in a given community. After reviewing the historical background of scholastic inclusion, the author presents its empirical, philosophical and ethical foundations. The concept of pedagogical inclusion proposed is based on five components with which various educational implications are associated. The article concludes by outlining the challenges and future perspectives of this pedagogy.